Penerapan Bimbingan Klasikal dengan Menggunakan Media Audiovisual Berbasis Podcast untuk Meningkatkan Motivasi Belajar Siswa Kelas VII A di SMP Negeri 1 Mengwi Tahun Pelajaran 2023/2024 - I Made Mahaardhika; I Wayan Nova Saputra; Ayu Made Nia Mahayani (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
This research aims to increase the learning motivation of class VII A students of SMP Negeri 1 Mengwi for the 2023/2024 academic year, where this research was conducted from November 2023 with a total of 5 students who had problems. The problem addressed in this research is that there are a number of students who lack motivation to participate in class learning. The type of research used is guidance and counseling action research (PTBK) with the application of podcast-based classical guidance methods to increase student learning motivation. In this counseling guidance action research, it was carried out in two cycles, namely cycle I and cycle II. The data analysis technique used in this research is a qualitative technique. Measuring the learning motivation scale, there were 5 students who experienced low student learning motivation. The research results obtained after the implementation of cycle I showed an average increase of around 48.4% to 71.8% with a group increase of 42.2%. In the second cycle, there was a significant increase ranging from 71.8% to 84.6%. When viewed as a group, there was an increase of 22.7%. Based on this description, it can be concluded that the Application of Classical Tutoring with Podcast-Based Audiovisual Media Can Increase the Learning Motivation of Class VII A Students at SMP Negeri 1 Mengwi for the 2023/2024 Academic Year.